Water, energy and food nexus in rice production in Thailand - Pitak Ngammuangtueng (2020)
© 2019 by the authors. This research introduces an approach to analyze the nexus of water, energy and rice production system at the watershed scale. The nexus relationship equations, developed to suit the local scale facilitating analysis in the rice production sector, were integrated with a Material Flow Analysis tool to expand the visualization capability. Moreover, the nexus flow was linked with the selected resource security, eco-efficiency and economic indicators, taking into account the spatial and temporal effect of water availability. The study covers the nexus resource flows not only in the rice production sector but also all other sectors in the whole watershed to assess local resource security. The tool covers wider implications, trade-offs and synergy impacts that were not much covered in previous studies. The tool was applied to evaluate the trade-offs and synergies of the impacts from proposed scenarios of alternative agricultural practices and land-use change options. The scenarios applying land-use change, and changing non-suitable and low-suitable rice cultivation areas to sugarcane and cassava, can reduce water use significantly resulting in reducing the nexus energy while the impact on economics, food security and direct energy use is small.